Risk Sharing and Information in Village Economies - Ligon, Ethan (Review of Economic Studies, 1998)
Arrangements for achieving efficient risk-sharing vary depending on the information available to agents in the economy. The usual Euler equation restricts efficient allocations in an economy which obeys the permanent income hypothesis, while efficient allocations in an economy with private information and long-term contracts satisfy a symmetric restriction, but not the Euler equation. Full insurance arrangements are unique in that they satisfy both restrictions. We look at an environment in which it seems likely that long-term contracts play a role in mitigating the effects of private information: three village economies in South India. The evidence that consumption allocations satisfy the private information restriction is quite strong for households in two of the three villages; the evidence for the third village suggests that while consumption for some households satisfies the private information restrictions, other households' consumption obey the permanent income hypothesis.